Reflective leadership by selected community college presidents - Stoeckel, Pamella Rae, author; Davies, Timothy Gray, advisor; Banning, James H., committee member; Hall, Bruce, committee member; Anderson, S. K., committee member (Colorado State University. Libraries, 2004)
This study examined community college presidents' self-reflective leadership. Community college presidents were chosen due to their critical role in leading institutions providing access to a majority of freshman and minority students entering higher education. A phenomenological approach answered the question: How is self-reflection experienced by community college presidents in the leadership role? Data was collected through in-depth interviews. Four female and four male presidents of diverse racial backgrounds were interviewed to uncover the lived experience of reflective leadership. Three themes emerged: mindfulness; discovery and authenticity. These themes revealed the essence of reflective leadership, self-care. Presidents spent deliberate time in introspection and inquiry, expanding self-awareness in order to lead others. This research expands knowledge of the community college presidents' role.
Keywords: higher education; community colleges; school administration; educational administration; community college education